Microalgae-bacterial granular consortium: Striding towards sustainable production of biohydrogen coupled with wastewater treatment. (June 2022) - Iqbal, Khushboo; Saxena, Abhishek; Pande, Priyanshi; Tiwari, Archana; Chandra Joshi, Naveen; Varma, Ajit; Mishra, Arti
Graphical abstract: Highlights: Overview of microalgae and bacteria for biohydrogen production. Biohydrogen production by a model system: Chlamydomonas reinhardtii. Review of recent development of microalgae and bacterial consortium in wastewater. Novel insight are essential for rapid hydrogen production commercialization. Abstract: Anthropogenic activities have drastically affected the environment, leading to increased waste accumulation in atmospheric bodies, including water. Wastewater treatment is an energy-consuming process and typically requires thousands of kilowatt hours of energy. This enormous energy demand can be fulfilled by utilizing the microbial electrolysis route to breakdown organic pollutants in wastewater which produces clean water and biohydrogen as a by-product of the reaction. Microalgae are the promising microorganism for the biohydrogen production, and it has been investigated that the interaction between microalgae and bacteria can be used to boost the yield of biohydrogen. Consortium of algae and bacteria resulting around 50–60% more biohydrogen production compared to the biohydrogen production of algae and bacteria separately. This review summarises the recent development in different microalgae-bacteria granular consortium systems successfully employed for biohydrogen generation. We also discuss the limitations in biohydrogen production and factors affecting its production from wastewater.